Constructed meaning: memes on social media among Muslim youth in Malaysia - Anuar, Faizul Nizar; Yusuf, Sarina; Jasni, Mohd Alif (Wolters Kluwer - Medknow Publications and Media Private Limited, 2022)
The development of communication technology today has changed the way people communicate and obtain information. Dependency on a certain type of media can be seen clearly when a crisis or tragedy happens in a country. Such dependency indirectly provides a picture of current issues that are occurring. This study focuses on the constructed meaning of memes on social media among Muslim youths in Malaysia. Memes sharing on social media will lead to meaning construction for the reader. The objective of this study is to identify the meaning constructed after the youths read the memes. A qualitative method through focus group interview was used to explore the information in this study. The focus group interview method was conducted at three Public Institution of Higher Learning, namely Putra University Malaysia, National University of Malaysia and the University of Malaya. Students majoring in Media and Communication Studies were selected by sampling for the purpose of this study. A total of 6 group interviews were conducted, and each group consists of 4 to 5 participants. The total number of informants in this study is 29 students. The theory used as the analytical concept is the Media Dependency Theory by Ball-Rokeach and DeFleur. The results of the study found that the meaning constructed after the youths read the memes are by sharing the memes, clicking the Unlike button, ignoring the memes, commenting, just reading the comments and lodging a report to the authorities.